2015
DOI: 10.1590/0034-737x201562050005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de genótipos de mandioca industriais em área de Cerrado do Noroeste de Minas Gerais

Abstract: A avaliação agronômica de cultivares é passo inicial para a determinação do potencial de cultivo de uma cultura em determinado local. Entretanto, ainda não foram desenvolvidos estudos sistemáticos visando à determinação do potencial produtivo de diferentes genótipos de mandioca para indústria, na região de Unaí, Minas Gerais. Por isso, o objetivo deste estudo foi avaliar, por duas safras, 12 genótipos-elite de mandioca para indústria de farinha e fécula, em área de Cerrado da Região Noroeste de Minas Gerais, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
1
0
2
Order By: Relevance
“…FCB Araújo et al 'Bitter' cassava had higher starch and sugar contents than the group of 'sweet' cassava ( Table 3). The starch contents were similar to those identified in another study with cassava accessions sampled in Brazil (Vieira et al 2015, Oliveira et al 2016.…”
Section: Resultssupporting
confidence: 85%
“…FCB Araújo et al 'Bitter' cassava had higher starch and sugar contents than the group of 'sweet' cassava ( Table 3). The starch contents were similar to those identified in another study with cassava accessions sampled in Brazil (Vieira et al 2015, Oliveira et al 2016.…”
Section: Resultssupporting
confidence: 85%
“…However, if the objective is shoot production, Sagrilo et al (2002) reported that, until 14 months after planting, the production averages of the total shoot remained constant, increasing until 17 months, with values approximately 50% higher than at the beginning of the harvest. Productivity is influenced by several factors, such as management, climate or soil but especially cultivars (Vieira et al, 2015), soil management (Filho et al, 2000), nutritional management (Alves Filho et al, 2015), cover plants (Otsubo et al, 2008), planting density (Tironi et al, 2019), harvest time (Mendonça et al, 2003), implantation time (Fagundes et al, 2010) pruning time (Aguiar et al, 2011a), weed control (Biffe et al, 2010), rainfall (Matos et al, 2016), temperature, photoperiod, and air humidity (Cury, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Na Tabela 1 estão apresentados os resultados dos experimentos com os valores médios e desvio padrão para cada parâmetro analisado na caracterização físico-química da crueira. Os resultados obtidos na Tabela 1 demonstram valores semelhantes aos apresentados por Neves [5] no que diz respeito ao teor de amido (81,1 ± 0,18%), lipídeos (0,44 ± 0,01%) e pH (5,4). Entretanto, demonstra diferenças com relação aos demais parâmetros físico-químicos pesquisados.…”
Section: Resultsunclassified
“…A mandioca, que é essencial para a agricultura brasileira e apresenta importante papel socioeconômico em vários países tropicais, é utilizada principalmente na produção de fécula e farinha [4]. No entanto, durante o seu processamento vários resíduos são gerados.…”
Section: Introductionunclassified